Baby signing time! Vol. 3, A new day [videorecording (DVD)]. - Coleman, Rachel (Two Little Hands Productions, 2008)
Alex, Leah, and Hopkins join Rachel Coleman to teach the signs for nature, weather, directions, and more. Songs include A new day, I'm a bug, Starry night, and Tiny hands.